2003
DOI: 10.1002/pssb.200301770
|View full text |Cite
|
Sign up to set email alerts
|

On the LO‐polaron dispersion in D dimensions

Abstract: We discuss the (LO)polaron dispersion for arbitrary spatial dimension D. Firstly, we review the existing literature; recent numerical work is critically analyzed. Secondly, we derive novel upper bounds for the dispersion, which incorporate the correct behaviour of the dispersion up to third order of the coupling constant a. A totally analytical evaluation is performed in the case D ¼ 1. We compare the upper bounds with previously published lower bounds. Apart from a surrounding of zero dispersion, the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…28,29 reported that their calculations were "numerically exact" and the error bars were smaller than the size of points at the plot. Previously, 15 we criticized these statements, in particular, because the results obtained give the wrong coefficient even in the second order in α for the polaron ground state energy weak-coupling expansion. As we could see above, the correct second order calculations are crucial for the adequate description of the dispersion near the edge point.…”
Section: The 3d Casementioning
confidence: 96%
See 1 more Smart Citation
“…28,29 reported that their calculations were "numerically exact" and the error bars were smaller than the size of points at the plot. Previously, 15 we criticized these statements, in particular, because the results obtained give the wrong coefficient even in the second order in α for the polaron ground state energy weak-coupling expansion. As we could see above, the correct second order calculations are crucial for the adequate description of the dispersion near the edge point.…”
Section: The 3d Casementioning
confidence: 96%
“…The only problem is that the numerical job becomes time consuming and could be done only for the case D = 1 (see Ref. 15 ). To conclude this section we mention a qualitatively different behavior of the dispersion curves for D = 1, 2 and D = 3.…”
Section: Basic Equationsmentioning
confidence: 99%
“…Early work on the behavior of the dispersion curve [16,17] allowed one to conclude that the energy-momentum relation starts off quadratically at low k (thus allowing one to define a polaron mass) but bends over when approaching the continuum edge E c (α) = E 0 (0,α) +hω 0 . Later it was found that in 3D the dispersion hits the continuum edge whereas for 2D it approaches it asymptotically, and upper and lower bounds for the dispersion were obtained [18][19][20]. These bounds, as well as some analytically known limits, constitute good benchmarks for any theory of the polaron dispersion.…”
Section: Introductionmentioning
confidence: 95%
“…Both large and small polarons have been observed in several experiments, as reported in the next section, and studied by simulations and computational techniques. Historically, large polarons have been investigated mostly via effective Hamiltonians, in particular by means of variational treatments solved by Feynmann's path integral techniques, and by diagrammatic Monte Carlo [27][28][29][40][41][42][43] approaches. First principles techniques are more suitable for the description of the small polaron, but successful attempts to address the large-polaron case have been presented in the last few years [11,44,45].…”
Section: Large Polaron Small Polaronmentioning
confidence: 99%